PENGARUH KONFLIK PERAN GANDA TERHADAP KINERJA MELALUI STRESS KERJA SEBAGAI MODERATOR PADA PEGAWAI WANITA - Abdul Wahab; Arfie Yasrie; Mahfuzil Anwar (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, Multiple role conflict or in other terms Work-Fanily Conflict for women who work and can not be avoided, because it is very strongly associated with depression as well as the traditional role of women who until now cannot be avoided, because it deals with responsibility in managing the household and raising child. There are two problems faced by women in multiple role conflicts, in this case on the one hand the family work conflict has the effect of decreasing household / family life, and on the other hand disrupts work activities. Based on the data obtained, the number of staff of the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Tabalong District which became the object of research specifically for female employees as many as 35 people became a sample of as many as the population of this study. Hypothesis 1, multiple role conflict has a positive effect on work stress stated to be acceptable, although not significant. Hypothesis 2, multiple role conflict has a positive effect on performance which is stated to be acceptable, although not significant. Hypothesis 3, Job stress is a moderator variable between multiple role conflict and performance.